3D Involute gear evaluation – Supplement: Measurements in double-flank contact. (May 2021) - Stein, Martin; Härtig, Frank
Highlights: Formulas relevant for double-flank contact gear measurements are provided. All equations are derived using a previously published 3D involute gear model. The sophisticated geometry is described in detail and illustrated by several figures. For the dimension over and between balls a reference value independent from the stylus radius is proposed. A numerical example illustrates the sensitivity of double-flank contact measurements to the sphere radius. Abstract: Equations for double-flank contact measurements as used in involute gear metrology are presented with their detailed mathematical derivations. All formulas can be applied to either internal or external and either spur or helical gears, even when considering profile shift. Moreover, a proposal for measurements using different stylus radii ensures comparability for the evaluation of the dimension over (or between) balls M dK . The influence of the stylus sphere radius on M dK is illustrated via a numerical example. All equations are derived for error-free gears. .